Identification of a Novel Papillomavirus in a Northern Fulmar (Fulmarus glacialis) With Viral Production in Cartilage. (May 2015) - Gaynor, A. M.; Fish, S.; Duerr, R. S.; Cruz, F. N. Dela; Pesavento, P. A.
We report the identification of a novel papillomavirus, Fulmarus glacialis papillomavirus 1 (FgPV1), present within an interdigital foot mass of a Northern Fulmar ( Fulmarus glacialis ). The mass of interest was composed of normal stratified and keratinized epithelium and dense mesenchymal cells with central cartilaginous islands. Within the nuclei of many chondrocytes were loose aggregates or paracrystalline arrays of virions approximately 50 nm in size. Degenerate polymerase chain reaction was used to identify the virus as a putative papillomavirus, and the entire viral genome of 8132 base pairs was subsequently amplified and sequenced. Analysis revealed canonical papillomavirus architecture, including the early open reading frames E6, E7, E1, and E2 and the 2 late proteins L1 and L2. FgPV1 is most closely related to a cluster of avian and reptilian papillomaviruses as visualized by phylogenetic trees. This observation suggests that papillomavirus virion production can occur in mesenchymal cells.